Inhabiting "necrofronteras": Afrojuvenicide in the Colombian Pacific - Rebolledo, Henry Steven (2023)
This article aims to analyze the elements that make up the landscapes and the conditions of precarization and death faced by Afro youth in the Colombian South Pacific, as part of the sociability dynamics of necropolitics and the global neoliberal project. The text is the result of an ethnographic research anchored in the participation in cultural organizations' spaces and the narratives of young people from the municipality of Tumaco, Nariño department, in the South Pacific region of Colombia. The theoretical developments presented here allow us to analyze the current forms of structural and direct violence against the precarious lives of young people, understanding the phenomenon of "juvenicide" that occurs in this region of the world and shapes the panorama of violence against Afro-Colombian youth. We will refer to this phenomenon as "afrojuvenicide," as part of the dynamics of necropolitics.